The Black Jacobins : Toussaint L'Ouverture and the San Domingo Revolution - James, Cyril Lionel Robert (New York : Vintage Books, 1963)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Castro, Fidel; Haïti; Cuba